2018
DOI: 10.1152/physiolgenomics.00052.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-fat diet feeding and associated transcriptome changes in the peak lactation mammary gland in C57BL/6 dams

Abstract: Maternal consumption of a high-fat diet (HFD) during pregnancy has established adverse effects on the developing neonate. In this study, we aimed to investigate the effect of an HFD on the murine mammary gland during midlactation. Female C57BL/6J mice were placed on either a low-fat diet (LFD/10% fat) or HFD (60% fat) from 3 wk of age through peak lactation (lactation day 11/L11). After 4 wk of consuming either the LFD or HFD, female mice were bred. There were no significant differences in milk yield between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…A hyperenergetic diet can alter the gene expression profile in the MG during lactation and thus modify the synthesis of milk components and subsequent milk composition. In particular, the expression of a variety of collagen genes was disrupted in the MG of female mice fed a high-fat diet, which is consistent with previous studies in other tissues such as the liver and heart [ 27 , 37 , 38 ]. After a high-fat diet, mammary tissue exhibits an inflammatory process that can lead to impaired synthesis and secretion of milk.…”
Section: Effects Of Energetic Supplementationsupporting
confidence: 90%
See 2 more Smart Citations
“…A hyperenergetic diet can alter the gene expression profile in the MG during lactation and thus modify the synthesis of milk components and subsequent milk composition. In particular, the expression of a variety of collagen genes was disrupted in the MG of female mice fed a high-fat diet, which is consistent with previous studies in other tissues such as the liver and heart [ 27 , 37 , 38 ]. After a high-fat diet, mammary tissue exhibits an inflammatory process that can lead to impaired synthesis and secretion of milk.…”
Section: Effects Of Energetic Supplementationsupporting
confidence: 90%
“…Moreover, MGs from lactating rats fed a high-fat diets displayed a disrupted morphology characterized by a few and small alveoli and were associated with a decrease in the transcription process in basal epithelial cells, which are important to the differentiation of the MG [ 26 ]. Although the measurement of milk production is difficult in models such as rodents, a high-fat diet consumed from puberty to mid-lactation showed no significant differences in milk yield during the first half of lactation [ 27 ]. Nevertheless, effects of high-fat diet tightly depend on species.…”
Section: Effects Of Energetic Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of collagen gene alterations on the lactating mammary gland and their subsequent effect on the infant is unknown. Two different studies have investigated collagen expression during peak lactation in mouse milk or the mammary gland, both demonstrating that an HFD alters collagen gene expression during peak lactation (5,6). Here we show that in general, Tph1-KO HFD mice have decreased collagen gene expression in comparison to WT-HFD mice.…”
Section: Discussionmentioning
confidence: 52%
“…A number of studies have reported that thousands of genes are differentially expressed by a high-fat diet as compared to a control diet (50)(51)(52)(53). We profiled global gene expression by RNA-Seq in three female mice fed the AIN-93M diet and three female mice fed a HFCA diet from each CC founder strains (n = 48 in total).…”
Section: Hepatic Transcriptomics Reveals Diet-specific Differences In the CC Progenitorsmentioning
confidence: 99%